2016
DOI: 10.5536/kjps.2016.43.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Quality Properties of Chicken Nugget with Various Levels of Chicken Skin

Abstract: This study aimed to investigate the effect of chicken skin on the proximate composition, pH, color, texture profile analysis, and sensory properties of chicken nugget. Chicken nugget samples were prepared by adding the following amount chicken skin 0% (control), 5%, 10% and 15%. The moisture and protein contents of the samples decreased with an increase chicken skin levels. And frying yield, redness, yellowness, Hardness, gumminess and chewiness of samples decreased with increasing chicken skin levels. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(10 reference statements)
4
0
0
2
Order By: Relevance
“… Biswas et al (2007) reported that a significant increase in fat levels of meat may be due to the addition of increased amounts of chicken skin in chicken sausage formulations. These results were consistent with those obtained by Kim et al (2016) for the addition of chicken skin to chicken nuggets. These studies also showed that the moisture content of samples decreased and the fat content increased with an increase in chicken skin levels.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“… Biswas et al (2007) reported that a significant increase in fat levels of meat may be due to the addition of increased amounts of chicken skin in chicken sausage formulations. These results were consistent with those obtained by Kim et al (2016) for the addition of chicken skin to chicken nuggets. These studies also showed that the moisture content of samples decreased and the fat content increased with an increase in chicken skin levels.…”
Section: Resultssupporting
confidence: 92%
“… Bhat et al (2013) reported that meatballs containing higher levels of chicken skin tended to show decrease in cooking yield, while a control sample without chicken skin gave the highest cooking yield after heating. Consistent with the results of this study, chicken nuggets with chicken skin also showed higher cooking loss than those without chicken skin ( Kim et al , 2016 ). These results may be attributable to the elution of fat and water from duck skin, and several studies have reported that cooking loss of meat products increased as skin content increased ( Biswas et al , 2007 ; Fotjik and Mandigo, 1998 ; Kim et al , 2016 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…닭고기는 고단백 저지방 식육자원(단백질: 20%, 지방: 5%) 으로 지난 30년간 소고기, 돼지고기와 닭고기 중 닭고기는 1인당 연간 소비량이 300% 가량 증가하였다 (Bonoli et al, 2007, Kim et al, 2016. 우리가 일반적으로 섭취하는 닭고기 는 브로일러(broiler)종으로 성장성이 우수하고 부드러운 육 질을 지니고 있어 상업적으로 가장 널리 이용되고 있다 .…”
Section: 서 론unclassified
“…(Key words: chicken breast ham, spent broiler breeder hen, spent laying hen, broiler) * These authors contributed equally to this work † To whom correspondence should be addressed : kimhy@kongju.ac.kr 서 론 닭고기는 고단백 저지방 식육자원(단백질: 20%, 지방: 5%) 으로 지난 30년간 소고기, 돼지고기와 닭고기 중 닭고기는 1인당 연간 소비량이 300% 가량 증가하였다 (Bonoli et al, 2007, Kim et al, 2016. 우리가 일반적으로 섭취하는 닭고기 는 브로일러(broiler)종으로 성장성이 우수하고 부드러운 육 질을 지니고 있어 상업적으로 가장 널리 이용되고 있다 .…”
unclassified